Stent for chronic total coronary occlusions: benefits and drawbacks after the introduction of drug-eluting stents. (June 2010) - Leo, Andrea; Giubilato, Simona; Bacà, Marco; Montone, Rocco Antonio; Niccoli, Giampaolo
Chronic total occlusion (CTO) is a common finding on diagnostic coronary angiography and constitutes one of the most challenging lesion subsets in interventional cardiology. The introduction of dedicated guidewires and the development of new techniques have improved the success rate in the crossing of CTO lesion while the use of bare-metal stents and drug-eluting stents has dramatically reduced the occurrence of restenosis and the need for target lesion revascularization in the short- and mid-term after CTO recanalization. However, new unsolved issues regarding the use of drug-eluting stents in CTO that might impact on long-term outcomes are emerging. The aim of this article is to review the current stage of knowledge on the application of stents in the treatment of CTO with a particular attention to the new complications associated with drug-eluting stent use in complex lesions.